Evaluation of Accounting Systems of Acceptance Premium and Payment of out of Contract Claims to Improve Internal Controls - susilowati MAB (Jurnal VOK@SINDO, 2014)
Implementation of the internal control system in an enterprise organization aims to preserve wealth, check the accuracy and reliability of accounting data, and to encourage efficiency and policy compliance management. The evaluation of accounting systems of acceptance premium and payment of out of contract claims at X Company is intended to provide input and suggestions for the accomplishment of the internal control system objectives. This study aims to investigate whether accounting systems of acceptance premium and payment of out of contract claims are already appropriate with the objectives of internal control. The method used was qualitative research with a case study approach. The result shows that there are some weaknesses in the implementation of accounting systems of acceptance premium and payment of out of contract claims. The systems are not consistent with the objectives of internal control. It is then suggested for the company to receive a premium in the form of a check on behalf of policy holders, so that collectors cannot do fraud. Additionally, for accounting system of advanced premium acceptance, it is suggested that Plan Visit sheet or PP.17 is copied and given a printed serial number. For accounting system of payment of out of contract claims, it is suggested that the agent is not involved in it. Also, service to policy holders, both in the implementation of premiums and payment of claims receipts, need to be improved